Pengembangan Perangkat Pembelajaran Model Problem Based Learning Melalui Penggunaan Bahan Manipulatif - Konstantinus Denny Pareira Meke; Maria Trisna Sero Wondo (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
This study aims to produce learning kits in the form of learning implementation plan and student worksheet on the probability material viewed from the learning outcomes and interest of learning mathematics. The learning kits were developed by applying the Problem Based Learning (PBL) model using manipulative materials. This type of research was development research with three core stages in the process, i.e. the initial research stage, the development stage and the assessment stage. The subjects in this study used one of mathematics teachers with 31 students of VIII grade of Maria Goretti Ende junior high school. Quantitative data in the form of scores from the assessment results were converted and analyzed into qualitative data in the form of five-scale standard scores. Data from expert validation showed that the gained learning kits produced met valid criteria. The teacher and student assessment scores showed that the learning kits had met many practical criteria. Furthermore, the results of the test scores and the results of the questionnaire scores indicated that Problem Based Learning learning using manipulative materials were effective in terms of learning outcomes and students' interest in learning mathematics. Based on these results, it can be concluded that the mathematics learning kits on the probability material is feasible to use.